2001
DOI: 10.1523/jneurosci.21-03-00999.2001
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Endothelin Receptors: Implications for the Involvement of Peripheral Glia in Nociception

Abstract: The endothelins (ETs) are peptides that have a diverse array of functions mediated by two receptor subtypes, the endothelin A receptor (ET A R) and the endothelin B receptor (ET B R). Pharmacological studies have suggested that in peripheral tissues, ET A R expression may play a role in signaling acute or neuropathic pain, whereas ET B R expression may be involved in the transmission of chronic inflammatory pain. To begin to define the mechanisms by which ET can drive nociceptive signaling, autoradiography and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
118
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(129 citation statements)
references
References 66 publications
11
118
0
Order By: Relevance
“…As ET receptor blockers were found to alleviate acute and chronic pain in several animal models, it was suggested that ETs have nociceptive effects [34,53]. Pomonis et al [135] investigated the distribution of ET receptors in DRG and found that only SGCs and non-myelinating Schwann cells expressed ET B receptors, whereas neurons expressed ET A receptors (see also Ref. [82]).…”
Section: Endothelinsmentioning
confidence: 99%
See 1 more Smart Citation
“…As ET receptor blockers were found to alleviate acute and chronic pain in several animal models, it was suggested that ETs have nociceptive effects [34,53]. Pomonis et al [135] investigated the distribution of ET receptors in DRG and found that only SGCs and non-myelinating Schwann cells expressed ET B receptors, whereas neurons expressed ET A receptors (see also Ref. [82]).…”
Section: Endothelinsmentioning
confidence: 99%
“…[82]). On the basis of evidence that ET B -deficient mice show reduced inflammatory response [58], it was proposed that SGCs may have a role in the transmission of pain signals [135]. Although based on indirect evidence, this intriguing idea is clearly worth pursuing.…”
Section: Endothelinsmentioning
confidence: 99%
“…ET-1 is found in high concentrations in dorsal root ganglion neurons and ET A receptors are found on small-to medium-sized root ganglion neurons and their axons (25). ET-1 enhances pain states in various models of acute chemicaland inflammation-induced pain and in chronic pain types such as neuropathic pain, where selective ET A inhibition shows preclinical efficacy (26).…”
Section: Ets and Their Receptorsmentioning
confidence: 99%
“…11 A recent study by Ukai et al reported that YM598, another selective ET A receptor antagonist, reduced NVCs in BOO rats. 13 Because NVCs in BOO rats are not affected by the treatment with the C-fiber neurotoxin resiniferatoxin, 13 the emergence of bladder overactivity in this model is thought to be primarily due to myogenic changes, rather than neurogenic changes in C-fibers. Thus, it seems that the suppressive effect of ET A receptor antagonists or ECE inhibitors on BOO-induced NVCs is induced by inhibition of smooth muscle activity, which was enhanced by upregulated ET mechanisms in the obstructed bladder.…”
Section: Commentmentioning
confidence: 96%